2012
DOI: 10.1073/pnas.1121546109
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin homolog TubZ in a phage-encoded partition system

Abstract: Partition systems are responsible for the process whereby large and essential plasmids are accurately positioned to daughter cells during bacterial division. They are typically made of three components: a centromere-like DNA zone, an adaptor protein, and an assembling protein that is either a Walker-box ATPase (type I) or an actin-like ATPase (type II). A recently described type III segregation system has a tubulin/FtsZ-like protein, called TubZ, for plasmid movement. Here, we present the 2.3 Å structure and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 31 publications
1
90
0
Order By: Relevance
“…Although different TubZRC systems have so far been observed to have considerable similarity (25,26), our Bt and Bm TubR complexes exhibit different curvatures. Bt TubRC crystallized as an extended DNA-protein filament with protein wrapping helically around the outside of the DNA, whereas the Bm TubR-DNA complex appears to form a ring or short helix with external DNA.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although different TubZRC systems have so far been observed to have considerable similarity (25,26), our Bt and Bm TubR complexes exhibit different curvatures. Bt TubRC crystallized as an extended DNA-protein filament with protein wrapping helically around the outside of the DNA, whereas the Bm TubR-DNA complex appears to form a ring or short helix with external DNA.…”
Section: Discussionmentioning
confidence: 98%
“…To confirm that the TubRC complex we had discovered was relevant to the activity of the TubZRC plasmid partitioning system, we assayed its effect on TubZ polymerization by 90°light scattering. A recent study by Oliva and colleagues (25) has shown that TubRC increases polymerization of TubZ. We therefore mixed Bt TubZ with GTP below the critical point of filament formation measurable by light scattering.…”
Section: Resultsmentioning
confidence: 99%
“…Additional components similar to organizing centers, spindle poles that anchor filaments as suggested for the PhuZ-based phage centering system (28), or other regulators may be required (29). One possibility for an anchor could be the nucleoid, and it has been noted that another gene, downstream of TubZRC, tubY (pBt158 on pBtoxis), might have DNA-binding activity and hence might be a candidate for this requirement (20). Alternately, at high intracellular TubZ concentrations, net growth could prevail, meaning a pushing mechanism is possible in principle.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of both truncated (iterons 1-3) and full-length (iterons 1-7) TubRC allowed for slow depolymerization and did not inhibit treadmilling. This effect explained the previously suggested stabilization effect of TubRC on filament formation (17,20). To check that the measured reduction in shrinkage was not caused by TubZ filament growth facilitated by bound TubRC, filaments were sequentially grown using differently labeled TubZ monomers, whereas TubR and tubC concentrations were kept constant.…”
Section: Tubrc Does Not Induce Insertional Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation